Measuring PROMIS® Emotional Distress in Early Childhood. (18th April 2022) - Sherlock, Phillip; Blackwell, Courtney K; Kallen, Michael A; Lai, Jin-Shei; Cella, David; Krogh-Jespersen, Sheila; Luby, Joan L; Buss, Kristin A; Burns, James; Wakschlag, Lauren S
Abstract: Objective: Create and validate developmentally sensitive parent-report measures of emotional distress for children ages 1–5 years that conceptually align with the Patient-Reported Outcome Measurement Information System (PROMIS ® ) pediatric measures. Methods: Initial items were generated based on expert and parent input regarding core components of emotional distress in early childhood and review of theoretical and empirical work in this domain. Items were psychometrically tested using data from two waves of panel surveys. Item response theory (IRT) was applied to develop item calibration parameters (Wave 1), and scores were centered on a general U.S. population sample (Wave 2). Final PROMIS early childhood (EC) instruments were compared with existing measures of related constructs to establish construct validity. Results: Experts and parents confirmed the content validity of the existing PROMIS Pediatric emotional distress domains (i.e., anger, anxiety, and depressive symptoms) as developmentally salient for young children. Existing items were adapted and expanded for early childhood by employing best practices from developmental measurement science. Item banks as well as 4- and 8-item short forms, free from differential item functioning across sex and age, were constructed for the three domains based on rigorous IRT analyses. Correlations with subscales from previously validated measures provided further evidence of construct validity. Conclusions: The PROMIS EC Anger/Irritability, Anxiety, and Depressive Symptoms measures demonstrated good reliability and initial evidence of validity for use in early childhood. This is an important contribution to advancing brief, efficient measurement of emotional distress in young children, closing a developmental gap in PROMIS pediatric emotional distress assessment.